The Implementation of Tourism Communication for Developing Tourismpreneurship and Destination Branding in Cijengkol Village, Subang - Mubarok, Muhamad Husni; Imaddudin (Community Development Journal, 2024)
Cijengkol Village in Subang Regency boasts significant local tourism potential, including the Cijengkol Seven Springs known for its water pH resembling infused water, and River Tubing, a popular activity along the upper stretch of the Ciasem river. This community service initiative aims to promote understanding of tourism entrepreneurship and destination branding, vital for harnessing local potential and enhancing regional tourist attractions. By encouraging environmental responsibility and fostering collaboration in developing regional tourism, the program seeks to empower Cijengkol Village residents. Effective tourism communication skills are seen as key to unlocking economic opportunities indirectly. The initiative addresses two main challenges: a lack of awareness regarding tourism's potential as a key sector, affecting micro, small, and medium enterprises, and underutilization of modern digital media for tourism communication. The approach involves specialized training for community members, particularly those involved in Village-Owned Enterprises (BUMDES) and Micro, Small, and Medium Enterprises (MSMEs) in Cijengkol Village. The outcome includes the formation of Tourism Awareness Group (Pokdarwis) candidates who understand a tourism vision and mission aligned with SMART goals for sustainable tourism management. Consequently, the candidates are equipped with collaborative concepts and strategies for tourism management in Cijengkol Village, serving as a foundation for future implementation.